Bioaccessibility and health risk of trace elements in fine particulate matter in different simulated body fluids. (August 2018) - Nie, Dongyang; Wu, Yun; Chen, Mindong; Liu, Huiling; Zhang, Kai; Ge, Pengxiang; Yuan, Yue; Ge, Xinlei
Abstract: Health risk assessment of trace elements (TrElems) in fine particulate matter (PM2.5 ) has been studied based on the total element concentrations or more recently on the phosphate buffered saline (PBS)-soluble concentrations. However, behaviors of the TrElems released from PM2.5 change considerably as the interacting media change. In this study, the bioaccessibility of particulate-bound TrElems (V, Mn, Co, Ni, Cu, As, Cd and Pb) were investigated using three kinds of simulated body fluids, artificial lung fluid (ALF), artificial sweat (AS), and artificial gastric juice (AGJ), comparing with the commonly used PBS. Many TrElems, especially Pb, showed lower solubility in PBS than that in other fluids. Cu, Mn, V and As were observed to be the most soluble TrElems in all simulated body fluids. Carcinogenic and non-carcinogenic effects were evaluated using ALF, AS and AGJ-soluble fractions (representing the corresponding exposure routes: inhalation, dermal contact and ingestion) according to the United States Environmental Protection Agency (USEPA) human health risk assessment model. The carcinogenic risks of As and Pb were higher than 1 × 10 −6 (the acceptable level) for both adults and children. High hazard quotient (HQ) values for As and Pb were also observed for children, indicating a potential non-carcinogenic risk posed by these toxic elements. Our results demonstrated that the health risks of particulate-bound TrElems might be misjudged if using the PBS-soluble or total element contents alone. Highlights: Bioaccessibility of PM2.5-bound TrElems were analyzed in three simulated body fluids. Health risks were assessed using ALF, AS and AGJ-soluble fractions. As and Pb showed potential carcinogenic and non-carcinogenic risks. Children were more sensitive than adults to PM2.5 exposure. Traditional evaluation methods might overestimate or underestimate the health risks.